ON THE INVERSIBILITY OF SOME FOURIER TYPE INTEGRAL OPERATORS - Khachatryan, I. G. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2004)
The paper considers in the space L^2(0, ∞) a Fourier type integral operator U, which arise in the inverse problem of the quantum scattering theory. It is proved, that either operator U or its conjugate U* is invertible.